Predictors of musculoskeletal pain among primary school students using smartphones in Nakhon Si Thammarat, Thailand - Mongkonkansai, Jittaporn; Veerasakul, Siriluk; Mohd Tamrin, Shamsul Bahri; Madardam, Uraiwan (MDPI, 2022)
School-age children increasingly use smartphones to conduct their learning activities; increasing reports of disorders related to smartphone use exist, including visual-related symptoms, stress, and musculoskeletal pain. This study aimed to examine risk factors for musculoskeletal pain among primary school students using smartphones. A cross-sectional study was conducted with 233 school-aged children in Nakhon Si Thammarat, Thailand. Data collection used a questionnaire for musculoskeletal symptoms using the Nordic Musculoskeletal Questionnaire with ISO 11,226:2000. Through Chi-square, t-test, and logistic regression analysis, factors independently associated with musculoskeletal pain were determined. An important factor in the development of musculoskeletal pain was the prolonged use of smartphones for longer than 60 min, particularly among children aged 6–9 years old. In regards to musculoskeletal pain, almost 53% of the students used their smartphones while lying down. Posing in a prone position while using a smartphone was 7.37 times more dangerous than sitting. The laying position tilts numerous organs at varying angles, especially the upper arm. The risk of musculoskeletal complaints must be reduced by educating parents, children, and the relevant government organizations about safe smartphone usage. The mentioned factors may be used to anticipate the onset of musculoskeletal pain caused by smartphone use in young children.